Questions of Military Safety in Programs of Parliamentary Parties during Elections to the State Duma of the VII convocation - Andrey Andreevich Kovalev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In Russia had taken place scheduled election campaign to State Duma. Each of «old» parliamentary parties submitted to voters the updated programs in which tried to reflect the views and positions on all topical issues of modern life of Russia. We are interested in place among these questions of a subject of military safety and that for its strengthening offer political parties today.